A STUDY ON ANTHELMINTIC ACTIVITY OF KUDAL PUZHU MATHIRAI - Sathya, V.; Shanmugapriya, C.; Gandhimathi, S.; Shameem, F. R. (International Journal of Ayurveda and Pharma Research, 2015)
Helminthic infections are the most common intestinal parasitic infections of human beings. Because of High prevalence, multidrug resistance, recurrence in nature it has been a challenge to completely eradicate the helminthic infection as of today. Ancient History reveals that many of herbals are used to cure the intestinal Helminthic infections. Hence the herbal preparation of drugs has built confidence among the modern people of today. Kudal puzhu Mathirai is a Siddha poly herbal formulation used for the treatment of worm infection. Most of the ingredients of KPM have anthelmintic, antispasmodic, anti-inflammatory & stomachic action. The aqueous extract of Kudal puzhu Mathirai [KPM] was investigated for anthelmintic activity using Adult earthworm (Eicinia fetida). Various concentration of KPM (200 mg/ml, 400mg/ml) were tested in the bioassay. Piperazine citrate (50mg/ml) was used as reference standard. Determination of paralysis time and death time of worms were recorded. The result showed that the Aqueous extract of KPM exhibited anthelmintic activity in dose-dependent manner taking shortest time for paralysis (P)=24 Min and death (D) =46 Min with 400mg /ml concentration.